1990
DOI: 10.1093/bja/65.3.353
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Effects of Propofol and of Thiopentone Anaesthesia in the Sheep

Abstract: We have examined the effects on the cardiovascular system and on regional blood flow of propofol and thiopentone when administered with IPPV (FIO2 0.4). A longitudinal study design was used in which 16 studies were performed in eight sheep for 30 min before, during the last 30 min of 70 min anaesthesia, and for 6 h after anaesthesia. During anaesthesia with propofol and thiopentone, mean total body oxygen consumption decreased, respectively, by 47% (P less than 0.001) and 24% (P less than 0.01) of pre-anaesthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 13 publications
6
24
0
Order By: Relevance
“…Isoflurane at 1 MAC also depresses mean arterial pressure in humans by ≈ 25%, mainly as a function of decreasing systemic vascular resistance with little effect on cardiac output ( Stevens et al ., 1971 ). Propofol at similar doses has been shown to increase heart rate and blood pressure without affecting cardiac output in sheep ( Runciman et al ., 1990 ).…”
Section: Discussionmentioning
confidence: 99%
“…Isoflurane at 1 MAC also depresses mean arterial pressure in humans by ≈ 25%, mainly as a function of decreasing systemic vascular resistance with little effect on cardiac output ( Stevens et al ., 1971 ). Propofol at similar doses has been shown to increase heart rate and blood pressure without affecting cardiac output in sheep ( Runciman et al ., 1990 ).…”
Section: Discussionmentioning
confidence: 99%
“…4 In contrast, studies in dogs established that propofol had no effect on HBF, HaBF, or PvBF. 5,8 As a final point, other animal studies have reported a reduction in hepatic blood flow 3,6,7 A number of explanations for these discrepancies are feasible: differences in drug dos- ‡P < 0.05 vs t 60 in the Group C; *P < 0.05 vs t 0 in the Group P; #P < 0.05 vs t 10 in the Group P. hDO 2 = total hepatic oxygen delivery; hVO 2 = total hepatic oxygen consumption; ShvO 2 = hemoglobin oxygen saturation in hepatic vein; ErO 2 = hepatic oxygen extraction ratio.…”
Section: Effect Of Propofol Infusion On Hepatic Blood Flowmentioning
confidence: 94%
“…Despite these limitations, with appropriate precautions, electromagnetic flowmeters provide an accurate measure of blood flow. 9,11 Studies measuring blood flow, using indirect methods such as indictor dye clearance 3,6,7 or radio labelled microspheres, 4,5 are susceptible to experimental error, and their calculations require numerous assumptions. 7,[9][10][11] One common finding is the apparent inhibition of the hepatic arterial buffer response.…”
Section: Effect Of Propofol Infusion On Hepatic Blood Flowmentioning
confidence: 99%
“…Although propofol has been reported to affect haemodynamics by negative inotropy and vasodilation, its effect on renal blood flow in healthy subjects is minimal 33,34 . While propofol may reduce renal function, similar to other anaesthetic compounds, in healthy animals, the depression in renal blood flow appears to be less than that during anaesthesia induction using volatile anaesthetics 35 .…”
Section: Discussionmentioning
confidence: 99%